2015
DOI: 10.3400/avd.cr.14-00083
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pulmonary Thromboembolism and Deep Vein Thrombosis during the Medical Treatment of Acute Aortic Dissection was Successfully Treated by the Combination of Inferior Vena Cava Filter Installation and Anti-Coagulant Therapy: A Case Report

Abstract: A 71-year-old woman was admitted with Stanford type A acute aortic dissection (AAD). Computed tomography (CT) revealed thrombosis of the false lumen, and we planned to treat medically. She developed transient pleural effusion and hypoxemia, which persisted despite her pleural effusion disappeared. We performed CT and found a large thrombus in the pulmonary artery and femoral vein. We administered low doseunfractionated heparin and installed a retrievable inferior vena cava fi lter, which caused the thrombus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In our case thrombolytic therapy was contraindicated and the convenience for the application of LMWH was uncertain. The vena cava filter should be a treatment option to prevent pulmonary embolism in such cases [10]. However in our case acute pulmonary embolism was present from the time of the DVT diagnosis.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In our case thrombolytic therapy was contraindicated and the convenience for the application of LMWH was uncertain. The vena cava filter should be a treatment option to prevent pulmonary embolism in such cases [10]. However in our case acute pulmonary embolism was present from the time of the DVT diagnosis.…”
Section: Discussionmentioning
confidence: 57%
“…It was suggested that during aortic dissection hypercoagulability may be triggered as a self-defence and this may cause thromboembolism [10]. VTE is a miscellaneous entity in the presence of acute aortic dissection therefore the anticoagulant or the thrombolytic therapy essential for the treatment of VTE may cause recanalization of the false lumen of the aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation